The Effect of Using Aids for Developing Shoulder Muscles’ Strength in Youth Martial Art Fighters - Qasim, Wissam; Sabah, Wafa (Journal of Physical Education, 2020)
The importance of the research lies in designing aids and rehabilitation exercises for developing shoulder joint strength that affects shoulder motor strength in youth martial art fighters. The problem of the research was fighters having injuries in rotator cuff muscles due to the requirement of this sports as well as the lack of using aids during rehabilitation. The researchers used the experimental method on (7) fighters using range of motion of (7) shoulder joint movements. The program was applied for (8) weeks with (3) rehabilitation sessions per week. The results showed that using special exercises using aids develop the muscular strength of rotator cuff in martial arts fighters.